Identification of 4‐lncRNA prognostic signature in head and neck squamous cell carcinoma. Issue 6 (11th December 2018) - Diao, Pengfei; Song, Yue; Ge, Han; Wu, Yaping; Li, Jin; Zhang, Wei; Wang, Yanling; Cheng, Jie
Abstract: Deregulated long noncoding RNAs (lncRNA) have been critically implicated in tumorigenesis and serve as novel diagnostic and prognostic biomarkers. Here we sought to develop a prognostic lncRNA signature in patients with head and neck squamous cell carcinoma (HNSCC). Original RNA‐seq data of 499 HNSCC samples were retrieved from The Cancer Genome Atlas database, which was randomly divided into training and testing set. Univariate Cox regression survival analysis, robust likelihood‐based survival model and random sampling iterations were applied to identify prognostic lncRNA candidates in the training cohort. A prognostic risk score was developed based on the Cox coefficient of four individual lncRNA imputed as follows: (0.14546 × expression level of RP11‐366H4.1) + (0.27106 × expression level of LINC01123) + (0.54316 × expression level of RP11‐110I1.14) + (−0.48794 × expression level of CTD‐2506J14.1). Kaplan‐Meier analysis revealed that patients with high‐risk score had significantly reduced overall survival as compared with those with low‐risk score when patients in training, testing, and validation cohorts were stratified into high‐ or low‐risk subgroups. Multivariate survival analysis further revealed that this 4‐lncRNA signature was a novel and important prognostic factor independent of multiple clinicopathological parameters. Importantly, ROC analyses indicated that predictive accuracy and sensitivity of this 4‐lncRNA signature outperformed those previously well‐established prognostic factors. Noticeably, prognostic score based on quantification of these 4‐lncRNA via qRT‐PCR in another independent HNSCC cohort robustly stratified patients into subgroups with high or low survival. Taken together, we developed a robust 4‐lncRNA prognostic signature for HNSCC that might provide a novel powerful prognostic biomarker for precision oncology. Abstract : This study revealed that risk score based on 4‐lncRNA signature significantly associates with patient survival in head and neck squamous cell carcinoma (HNSCC).